2012
DOI: 10.1111/j.2041-210x.2012.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversitree: comparative phylogenetic analyses of diversification in R

Abstract: Summary1. The R package 'diversitree' contains a number of classical and contemporary comparative phylogenetic methods. Key included methods are BiSSE (binary state speciation and extinction), MuSSE (a multistate extension of BiSSE), and QuaSSE (quantitative state speciation and extinction). Diversitree also includes methods for analysing trait evolution and estimating speciation/ extinction rates independently. 2. In this note, I describe the features and demonstrate use of the package, using a new method, Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
917
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 849 publications
(924 citation statements)
references
References 39 publications
(45 reference statements)
6
917
0
1
Order By: Relevance
“…8 and Supplementary Note). To test whether high MHC I copy numbers are associated with lineages that have high diversification rates, we carried out BiSSE analyses 68 with the diversitree R package 69 . In these analyses, species were grouped into two categories for high and low MHC I copy numbers, on the basis of a given threshold value.…”
Section: Methodsmentioning
confidence: 99%
“…8 and Supplementary Note). To test whether high MHC I copy numbers are associated with lineages that have high diversification rates, we carried out BiSSE analyses 68 with the diversitree R package 69 . In these analyses, species were grouped into two categories for high and low MHC I copy numbers, on the basis of a given threshold value.…”
Section: Methodsmentioning
confidence: 99%
“…MCMC sampling of the BiSSE model (31,33) indicates that migration was lost at a significantly higher rate than gained (SI Materials and Methods).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, specialization on particular host species has led to genetic divergence within some cuckoo and honeyguide species into distinct host-specific races [16][17][18], and Krü ger et al [19] demonstrated that species of parasitic cuckoos had more subspecies than species of non-parasitic cuckoos. Since the appearance of these studies, novel phylogenies [20] and phylogenetic methods [3,21] have been developed.…”
Section: Introductionmentioning
confidence: 99%